Bulletin of the fifth congress of the Communist International
Continues (ZF 16017) and continued by: Bulletin of the Enlarged executive of the Communist International (ZF 16022). - French ed.: Bulletin du V-e congrès de l'Internationale Communiste. (ZF 16018). - German ed.: Bulletin des V. Kongresses der Kommunistischen Internationale (ZF 16020).